Comprehensive Mass Cytometry Analysis of Cell Cycle, Activation, and Coinhibitory Receptors Expression in CD4 T Cells from Healthy and HIV‐Infected Individuals. Issue 1 (January 2017) - Corneau, Aurélien; Cosma, Antonio; Even, Sophie; Katlama, Christine; Le Grand, Roger; Frachet, Véronique; Blanc, Catherine; Autran, Brigitte
Abstract : Rationale: Mass cytometry allows large multiplex analysis of cell cycle stages together with differentiation, activation, and exhaustion markers, allowing further assessment of the quiescence status of resting CD4 T cells. Methods: Peripheral blood CD4 T lymphocytes from 8 individuals, 4 healthy donors, and 4 HIV‐infected on antiretroviral treatment (T) were stained with the same 26 monoclonal antibodies and dyes targeting surface and intracellular markers of differentiation, activation, exhaustion, and cell cycle stages. Samples were run on a CYTOF‐2. Results: Patterns of naïve [TN] CD4 T cells strongly differed from all other memory subsets central‐memory (CM), transitional‐memory (TM), effector‐memory (EM), and terminally differentiated RA‐expressing (TEMRA) subsets, while stem‐cell memory (SCM) and T follicular‐helper cells (TfH) were close to CM and TM cells with the highest percentages in cell cycle. EM and TEMRA were the most altered by HIV infection, with an increased frequency of activated and cycling cells. Activation markers and coinhibitory receptor expression differed among cell cycle stages, with HLA‐DR fitting better than CD25 or CD38 with cycle, and opposite PD‐1 gradients along differentiation and cell cycle. "Resting" DR‐CD25‐ CD4+ T cells contained similar amounts of cells in G1 than the activated DR ± CD25± ones but three fold lower cells in S‐G2‐M. Conclusion: This broad multiplex mass cytometry analysis demonstrates some subsets of the so‐called "resting" CD25‐DR‐ CD4+ T cells contain noticeable amounts of cells into cycle or expressing coinhibitory receptors, opening new avenues for a redefinition of resting peripheral blood CD4 T cells harboring the HIV reservoirs. © 2016 International Clinical Cytometry Society